Multicomponent Cu-Ni-Sn-based alloy for oil and gas extraction and its manufacturing method
Patent Information
- Application Number
- JP2023579625
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-23
- Filing Date
- 2022-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-29
AI Technical Summary
【0009】 本発明の石油およびガス採取用多元Cu-Ni-Sn基合金に対しては、以下の有益な効果を有する。(1)合金成分が均一であり、鋳造状態ミクロ組織のデンドライト間隔が小さくなり、分布がより均一であり、且つ配置方向がより一致する。(2)優れた力学性能:強度が1000MPa以上であり、伸び率が3%以上である。(3)優れた耐摩耗性能:磨耗率が0.1mg/m以下である。本発明の石油およびガス採取用多元Cu-Ni-Sn基合金は、特に石油およびガス採取の鍵となる部材への応用に適している。
Smart Images

Figure 0007630856000002 
Figure 0007630856000003 
Figure 0007630856000004
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of metal materials technology, specifically to a multi-component Cu-Ni-Sn-based alloy for oil and gas extraction and its manufacturing method. [Background technology]
[0002] Copper alloys have good conductivity, mechanical properties, cold / hot processing properties, wear resistance and corrosion resistance, and are often used as functional structural integration materials in electronic information, rail transportation, marine engineering, oil and gas extraction and other fields. However, the petroleum and petrochemical industry is an important support for the development of the national economy. Oil drilling MWD, LWD drilling tools, oil drilling guide rods, electric pump assemblies, exploration probes, deep sea explosion-proof, separable connection valves and other various oil drilling tools and equipment components are mainly made of copper alloy materials, which require high strength, high wear resistance, high temperature resistance, non-magnetic explosion-proof and other properties under harsh working conditions such as high temperature, high pressure, high load and high stability. For a long time, the improvement of the high strength, wear resistance and durability of copper alloy materials used in the above fields is a key problem that plagues the development of the industry.
[0003] Commonly used wear-resistant copper alloys mainly include brass, tin bronze, aluminum bronze, beryllium bronze, etc. However, Cu-Ni-Sn-based alloys have excellent mechanical properties, wear resistance and corrosion resistance, and are therefore widely used in the fields of petroleum and natural gas, marine engineering, electronics and electrical appliances, and machinery manufacturing. However, due to the high Sn content, low melting point, and wide alloy crystallization temperature range in this alloy system, macro-component segregation and micro-dendrite segregation are likely to occur under normal melt casting conditions, which is unfavorable for subsequent processing deformation, and at the same time, it is difficult to improve the overall performance of the material. Therefore, how to combine the improvement of the melt casting process through alloy design, suppress the composition and microstructural segregation based on Cu-Ni-Sn alloy, and improve the strength and wear resistance is of great significance for the development of high-performance copper alloy materials for oil and gas extraction.
[0004] Therefore, there is a need to provide an improved technical solution to address the shortcomings of the prior art. Summary of the Invention [Problem to be solved by the invention]
[0005] The objective of the present invention is to provide a multi-component Cu-Ni-Sn-based alloy for oil and gas extraction and a manufacturing method thereof, which solves or improves at least one of the problems of the prior art, namely, that the Cu-Ni-Sn alloy is prone to macro-component segregation or micro-dendrite segregation, that it is disadvantageous in subsequent processing deformation, and that it is necessary to improve the strength and wear resistance. [Means for solving the problem]
[0006] In order to achieve the above object, the present invention provides the following technical solution: A multi-component Cu-Ni-Sn-based alloy for oil and gas extraction, containing, by weight, Ni: 7-20%, Sn: 4-12%, Si: 0.3-1.2%, Al: 0.2-3.0%, Nb: 0.02-0.5%, Mn: 0.2-2.0%, Fe: 0.2-2.0%, and the balance being Cu.
[0007] The present invention further provides a method for producing the above-mentioned multi-element Cu-Ni-Sn-based alloy for oil and gas extraction, which adopts the following technical scheme. The method for producing the above-mentioned multi-element Cu-Ni-Sn-based alloy for oil and gas extraction includes the following steps: first, add electrolytic copper to a melting furnace, completely melt the electrolytic copper, then add Ni source, further add Nb source, Mn source, Fe source and Si source, and finally add Al source and Sn source, and melt at 1150-1250°C for 30-50 min; step (1) is melting; the molten metal processed in step (1) is made mirror-like, then left to stand for 1-3 min, and after the standing is completed, the molten metal is poured into a metal mold, solidified, and an ingot is obtained; and step (3) is uniform annealing, hot extrusion deformation, solution heat treatment, cold wire drawing deformation and aging heat treatment on the ingot. Beneficial effects
[0008] The present invention uses micro-alloying to add a variety of alloying elements such as silicon (Si), aluminum (Al), niobium (Nb), manganese (Mn), and iron (Fe) to the Cu-Ni-Sn alloy substrate, and improves the micro-segregation in the alloy solidification structure under the cooperative action of a variety of elements, and jointly improves the strength and wear resistance of the alloy. However, the addition of Si element can inhibit the formation of reverse segregation during alloy solidification, obtain fine grains, and improve the hot / cold processing performance of the alloy, and Si and Ni form a series of NiSi strengthening phases to enhance the alloy strength. Al element and Ni element form a series of NiAl strengthening phases, which can significantly improve the mechanical performance of the alloy. Nb element promotes the amplitude modulation decomposition process of the alloy, improves the resistance recovery and recrystallization softening ability of the alloy, and forms Nb-rich γ phase in the crystal and crystal boundary, which can significantly inhibit the growth of crystal grains and the formation of discontinuous precipitation during the aging process, and improve the alloy strength and wear resistance. The Mn element can refine the grain structure in the as-cast state, increase the peak strength of the alloy during age hardening, and inhibit grain boundary reaction and grain coarsening, thereby significantly improving the strength and wear resistance of the alloy. The addition of a trace amount of Fe can accelerate the deformation heat treatment process of the alloy, and improve the strengthening effect and wear resistance.
[0009] The multi-component Cu-Ni-Sn-based alloy for oil and gas extraction of the present invention has the following beneficial effects: (1) The alloy components are uniform, the dendrite spacing of the microstructure in the as-cast state is smaller, the distribution is more uniform, and the arrangement direction is more consistent. (2) Excellent mechanical performance: the strength is 1000 MPa or more, and the elongation rate is 3% or more. (3) Excellent wear resistance: the wear rate is 0.1 mg / m or less. The multi-component Cu-Ni-Sn-based alloy for oil and gas extraction of the present invention is particularly suitable for application to key components for oil and gas extraction. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a microstructure diagram of a conventional Cu-15Ni-8Sn alloy. [Diagram 2]FIG. 2 is a microstructure diagram of the multi-component Cu—Ni—Sn-based alloy for oil and gas extraction produced according to Example 1 of the present invention. [Diagram 3] FIG. 2 is a microstructure diagram of the multi-component Cu—Ni—Sn-based alloy for oil and gas extraction produced according to Example 2 of the present invention. [Figure 4] FIG. 2 is a microstructure diagram of the multi-component Cu—Ni—Sn-based alloy for oil and gas extraction produced according to Example 3 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below by combining embodiments. In addition, the embodiments of the present invention and the features of the embodiments may be combined with each other if there is no conflict.
[0012] In response to at least one of the problems of the prior art Cu-Ni-Sn alloys being prone to macro-component segregation or micro-dendrite segregation, being disadvantageous in subsequent processing deformation, and needing to have improved strength and wear resistance, the present invention provides a multi-component Cu-Ni-Sn-based alloy for oil and gas production, which contains, by weight percent, 7-20% Ni, 4-12% Sn, 0.3-1.2% Si, 0.2-3.0% Al, 0.02-0.5% Nb, 0.2-2.0% Mn, and 0.2-2.0% Fe, with the balance being Cu.
[0013] In a preferred embodiment of the present invention, the contents of the trace elements O, S and P in the multi-component Cu-Ni-Sn-based alloy for oil and gas production are less than 5 ppm for O, less than 3 ppm for S and less than 3 ppm for P, respectively.
[0014] In a preferred embodiment of the present invention, the multi-component Cu-Ni-Sn based alloy for oil and gas extraction contains, by weight, 15% Ni, 8% Sn, 0.8% Si, 1.2% Al, 0.3% Nb, 0.5% Mn, and 0.5% Fe, with the balance being Cu.
[0015] In a preferred embodiment of the present invention, the multi-component Cu-Ni-Sn based alloy for oil and gas extraction has a tensile strength of 1000 MPa or more, an elongation of 3% or more, and a wear rate of 0.1 mg / m or less.
[0016] The present invention further provides a method for producing a multi-element Cu-Ni-Sn-based alloy for oil and gas extraction. The method for producing a multi-element Cu-Ni-Sn-based alloy for oil and gas extraction according to an embodiment of the present invention includes the following steps: Step (1) is melting, in which electrolytic copper is first added to a melting furnace, and the electrolytic copper is completely melted, and then a Ni source is added, and then a Nb source, a Mn source, a Fe source, and a Si source are added, and finally an Al source and a Sn source are added, and the mixture is melted at 1150-1250°C for 30-50 min; Step (2) is pouring, in which the molten metal processed in Step (1) is made mirror-like and then left to stand for 1-3 min, and after the standing is completed, the molten metal is poured into a metal mold to solidify the molten metal and obtain an ingot; and Step (3) is performing uniform annealing, hot extrusion deformation, solution heat treatment, cold wire drawing deformation, and aging heat treatment on the ingot.
[0017] In a preferred embodiment of the method for producing a multi-component Cu-Ni-Sn-based alloy for oil and gas extraction of the present invention, in step (1), the Cu in the electrolytic copper is 99.95 wt% or more, the Ni source is electrolytic nickel, and the Ni in the electrolytic nickel is 99.96 wt% or more, the Nb source is a Cu-Nb intermediate alloy, the Mn source is a Cu-Mn intermediate alloy, the Fe source is a Cu-Fe intermediate alloy, the Si source is pure silicon, and the Si is 99.99 wt% or more, the Al source is pure aluminum, and the Al is 99.7 wt% or more, and the Sn source is pure tin, and the Sn is 99.99 wt% or more.
[0018] In the preferred embodiment of the method for producing the multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of the present invention, in step (1), in the melting furnace, the melt surface is completely covered with charcoal, and (during the melting process) pure phosphorus deoxidizer is used for deoxidation, in which the phosphorus content is 99.85%-99.95%, and the amount of the pure phosphorus deoxidizer used is 0.1%-0.5% of the total weight of the molten metal, and the melting process also includes the steps of stirring with a graphite stirring rod and scraping off the slag with a slag scraping rod. However, since phosphorus element preferentially reacts with oxygen in the melt, adding an appropriate amount of pure phosphorus deoxidizer can play a role in purifying the melt, but if the amount added is too high (more than 0.5% of the total weight of the melt), too much phosphorus will remain in the alloy, which will increase the brittleness of the material and be disadvantageous to the subsequent plastic deformation.
[0019] In a preferred embodiment of the method for producing a multi-element Cu-Ni-Sn-based alloy for oil and gas extraction according to the present invention, in step (2), the temperature of the pouring is 1200-1300°C, and after the pouring is completed, the step of applying an electromagnetic field outside the metal mold is also included, and the current applied range of the electromagnetic field is 20-100A. However, the pouring temperature is an important parameter in the melting and casting stage of the material, and if the pouring temperature is too low, the fluidity of the melt is poor, and casting defects such as pouring failure, shrinkage, holes, and cold partitions are likely to occur. If the pouring temperature is too high, it will cause element burnout, while the crystal grains of the solidification structure will become coarse, resulting in poor performance. The strength of the electromagnetic field is mainly controlled by adjusting the magnitude of the current, which mainly affects the magnitude of the stirring force that the electromagnetic field exerts on the melt, and the magnitude of the stirring force is further directly related to the degree of destruction of the formation of the dendritic structure in the solidification process. Therefore, the electromagnetic field strength can be controlled by different current magnitudes, which further influences the formation and distribution of Sn-rich gamma phase, suppresses the effects of dendritic segregation, and improves the subsequent overall performance of the alloy.
[0020] The present invention improves the segregation of the as-cast solidification structure by selecting micro-alloying elements and combining with electromagnetic stirring. The quality of the as-cast structure directly affects the difficulty of the subsequent processing steps and the overall performance of the final material.
[0021] In a preferred embodiment of the method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas extraction of the present invention, the temperature of the uniform annealing is 900-950°C, the temperature of the hot extrusion deformation is 850-950°C, the temperature of the solution heat treatment is 750-900°C, the amount of cold wire drawing deformation is 50-90%, and the temperature of the aging heat treatment is 300-500°C.
[0022] The multi-component Cu-Ni-Sn-based alloy for oil and gas extraction and the manufacturing method thereof according to the present invention will be described in detail below with reference to specific examples.
[0023] Example 1 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight, Ni: 9%, Sn: 6%, Si: 1.2%, Al: 3%, Nb: 0.5%, Mn: 2.0%, and Fe: 2.0%, and the other trace elements O, S, and P are, respectively, O: 5 ppm or less, S: 3 ppm or less, P: 3 ppm or less, and the balance is Cu.
[0024] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0025] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0026] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0027] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1150°C and the duration is 50 minutes.
[0028] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.1% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0029] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for 1 minute, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1200°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 20A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0030] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 900°C, the temperature of the hot extrusion deformation is 850°C, the temperature of the solution heat treatment is 750°C, the amount of cold wire drawing deformation is 50%, and the temperature of the aging heat treatment is 300°C.
[0031] The microstructure of the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment is shown in FIG.
[0032] The multi-component Cu-Ni-Sn-based alloy for oil and gas extraction produced by this embodiment has uniform composition, and its microstructure in the as-cast state has smaller dendrite spacing than that of the conventional Cu-15Ni-8Sn alloy, and has a tensile strength of 1035 MPa, an elongation of 6.9%, and a wear rate of 0.09 mg / m.
[0033] However, for the observation of the microstructure, the usual testing methods commonly used in the fields of materials science and engineering are adopted. First, the manufactured sample is cut and sampled, then polished and etched, and the microstructure morphology is observed using a Zeiss Axio Vert A1 optical microscope.
[0034] Example 2 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight, Ni: 15%, Sn: 8%, Si: 0.8%, Al: 1.2%, Nb: 0.3%, Mn: 0.5%, and Fe: 0.5%, with the other trace elements O, S, and P being 5 ppm or less, 3 ppm or less, and 3 ppm or less, respectively, with the balance being Cu.
[0035] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0036] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0037] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0038] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1200°C and the duration is 40 minutes.
[0039] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.3% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0040] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for 3 minutes, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1250°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 50A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0041] However, before pouring the molten metal into the mold, the metal mold is preheated to a preheat temperature of 300°C.
[0042] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 920°C, the temperature of the hot extrusion deformation is 900°C, the temperature of the solution heat treatment is 840°C, the amount of cold wire drawing deformation is 70%, and the temperature of the aging heat treatment is 420°C.
[0043] The microstructure diagram of the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment is shown in FIG.
[0044] The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction manufactured in this embodiment has uniform composition, and the microstructure of the as-cast alloy has smaller dendrite spacing, more uniform distribution, and more consistent orientation than the conventional Cu-15Ni-8Sn alloy. The mechanical and wear resistance tests show that the tensile strength is 1150 MPa, the elongation is 4.1%, and the wear rate is 0.02 mg / m.
[0045] Example 3 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight, Ni: 20%, Sn: 12%, Si: 0.3%, Al: 0.2%, Nb: 0.02%, Mn: 0.2%, and Fe: 0.2%, with the other trace elements O, S, and P being 5 ppm or less, 3 ppm or less, and 3 ppm or less, respectively, with the balance being Cu.
[0046] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0047] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0048] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0049] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1250°C and the duration is 30 minutes.
[0050] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.5% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0051] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for 1 minute, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1300°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 100A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0052] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 950°C, the temperature of the hot extrusion deformation is 950°C, the temperature of the solution heat treatment is 900°C, the amount of cold wire drawing deformation is 90%, and the temperature of the aging heat treatment is 500°C.
[0053] The microstructure diagram of the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment is shown in FIG.
[0054] The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction produced in this embodiment has uniform composition, and the microstructure of the as-cast alloy has smaller dendrite spacing than the conventional Cu-15Ni-8Sn alloy. The mechanical and wear resistance tests show that the alloy has a tensile strength of 1092 MPa, an elongation of 5.3%, and an abrasion rate of 0.06 mg / m.
[0055] Example 4 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight percent, Ni: 7%, Sn: 4%, Si: 1.2%, Al: 3.0%, Nb: 0.5%, Mn: 2.0%, and Fe: 0.8%, and the other trace elements O, S, and P are, respectively, 4 ppm or less for O, 3 ppm or less for S, 3 ppm or less for P, and the balance being Cu.
[0056] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0057] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0058] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0059] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1200°C and the duration is 40 minutes.
[0060] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.5% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0061] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for 1 minute, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1250°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 90A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0062] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 920°C, the temperature of the hot extrusion deformation is 930°C, the temperature of the solution heat treatment is 870°C, the amount of cold wire drawing deformation is 85%, and the temperature of the aging heat treatment is 400°C.
[0063] The multi-element Cu-Ni-Sn-based alloy for oil and gas production produced by this embodiment has uniform composition, and the microstructure of the as-cast alloy has smaller dendrite spacing than the conventional Cu-15Ni-8Sn alloy. The tensile strength is 1033 MPa, the elongation is 7.1%, and the wear rate is 0.09 mg / m.
[0064] Example 5 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight, Ni: 12%, Sn: 10%, Si: 0.5%, Al: 2.4%, Nb: 0.08%, Mn: 0.8%, and Fe: 2.0%, and the other trace elements O, S, and P are, respectively, O: 5 ppm or less, S: 3 ppm or less, P: 3 ppm or less, and the balance is Cu.
[0065] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0066] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0067] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0068] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1250°C and the duration is 30 minutes.
[0069] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.4% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0070] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for one minute, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1300°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 85A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0071] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 900°C, the temperature of the hot extrusion deformation is 920°C, the temperature of the solution heat treatment is 840°C, the amount of cold wire drawing deformation is 80%, and the temperature of the aging heat treatment is 420°C.
[0072] The multi-element Cu-Ni-Sn-based alloy for oil and gas production produced by this embodiment has uniform composition, and the microstructure of the as-cast alloy has smaller dendrite spacing than the conventional Cu-15Ni-8Sn alloy. The tensile strength is 1148 MPa, the elongation is 4.5%, and the wear rate is 0.03 mg / m.
[0073] Example 6 The multi-element Cu-Ni-Sn-based alloy for oil and gas extraction of this embodiment is composed of, by weight, Ni: 20%, Sn: 4%, Si: 0.3%, Al: 0.2%, Nb: 0.02%, Mn: 0.2%, and Fe: 0.2%, with the other trace elements O, S, and P being 4 ppm or less, 3 ppm or less, and 3 ppm or less, respectively, with the balance being Cu.
[0074] The method for producing the multi-component Cu-Ni-Sn-based alloy for oil and gas production of this embodiment includes the following steps (1) to (5).
[0075] In step (1), which is the preparation of raw materials, the following materials are selected and used: 1# electrolytic copper (Cu≧99.95%), 1# electrolytic nickel (Ni≧99.96%), pure tin (Sn≧99.99%), pure silicon (Si≧99.99%), pure aluminum (Al≧99.7%), Cu-Nb intermediate alloy, Cu-Mn intermediate alloy and Cu-Fe intermediate alloy produced by Henan Yixin Non-ferrous Metal Materials Co., Ltd., and then cut, dried and treated to remove surface oil, and are ready for use.
[0076] In step (2) of preparing the raw materials, the raw materials processed in step (1) are weighed to produce the multi-element Cu-Ni-Sn-based alloy of this example.
[0077] In the casting step (3), electrolytic copper is first added to the melting furnace, and then heated to melt the electrolytic copper, followed by adding pure nickel, followed by adding Cu-Nb intermediate alloy, Cu-Mn intermediate alloy, Cu-Fe intermediate alloy and pure silicon, and finally adding pure aluminum and pure tin. The melting temperature is 1180°C and the duration is 35 minutes.
[0078] In the heating and melting process, the molten liquid surface is completely covered with charcoal, and the charcoal cover layer blocks most of the air, realizing the melting process to be carried out in a slightly oxidizing atmosphere. In the melting process, pure phosphorus deoxidizer is used for deoxidation, with a phosphorus content of 99.85%-99.95%, and the amount of pure phosphorus deoxidizer used is 0.5% of the total weight of the molten metal. In the melting process, a graphite stirring rod is used for stirring, and a slag scraping rod is used to scrape off the slag.
[0079] In step (4) of pouring, after no scum appears on the surface of the molten metal and the surface of the molten metal is polished to a mirror-like finish, the molten metal is left to stand for 1 minute, and then the molten metal is directly poured into the metal mold at a pouring temperature of 1210°C. At the same time, in order to further improve the solidification structure segregation, an electromagnetic field is applied outside the metal mold, and after the molten metal is poured into the metal mold, the magnitude of the acting force is changed by adjusting the current of the electromagnetic field, and an external force is exerted on the melt solidification process, and the applied current range is 75A. Under the combined action of the electromagnetic field and the cooling device, the molten metal solidifies to obtain an ingot.
[0080] In step (5), the ingot with a uniform structure produced by fusion casting is subjected to the following steps: uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment, where the temperature of the uniform annealing is 910°C, the temperature of the hot extrusion deformation is 900°C, the temperature of the solution heat treatment is 830°C, the amount of cold wire drawing deformation is 75%, and the temperature of the aging heat treatment is 370°C.
[0081] The multi-element Cu-Ni-Sn-based alloy for oil and gas production produced by this embodiment has uniform composition, and the microstructure of the as-cast alloy has smaller dendrite spacing than the conventional Cu-15Ni-8Sn alloy. The tensile strength is 1076 MPa, the elongation is 4.9%, and the wear rate is 0.05 mg / m.
[0082] Comparative Example 1 The ordinary Cu-15Ni-8Sn alloy of this comparative example is composed, by weight, of 15% Ni and 8% Sn, with the remainder being Cu.
[0083] The conventional Cu-15Ni-8Sn alloy of this comparative example is produced by a method including the following steps.
[0084] A non-vacuum melting furnace is used to melt electrolytic copper (Cu≧99.95%), electrolytic nickel (Ni≧99.96%), and pure tin (Sn≧99.99%), and no alloying elements such as Al, Nb, Mn, and Fe are added in the melting process, which is favorable for the segregation of solidification structure and the improvement of performance. At the same time, the control range for other trace elements O, S, and P is relatively wide, and generally, the content of O is greater than 10 ppm, the content of S is greater than 8 ppm, and the content of P is greater than 8 ppm. After the melt is completely melted, it is directly poured into a metal mold, and solidified by cooling without electromagnetic field stirring to obtain an ingot. Then, the subsequent uniform annealing → hot extrusion deformation → solution heat treatment → cold wire drawing deformation → aging heat treatment is carried out. The normal process has serious segregation problems in the solidification structure at the melting casting stage, which makes the subsequent deformation even more difficult and reduces the material yield. However, the uniform annealing temperature is 950°C, the hot extrusion deformation temperature is 950°C, the solution heat treatment temperature is 900°C, the cold wire drawing deformation amount is 90%, and the aging heat treatment temperature is 500°C.
[0085] Comparative Example 2 The difference between this comparative example and Example 1 is only in that the amount of added Si element was 0.28% (less than 0.3%), and all other points are the same as those of Example 1.
[0086] Comparative Example 3 The difference between this comparative example and Example 2 is only in that the amount of Al element added was 0.19% (less than 0.2%), and all other points are the same as those of Example 2.
[0087] Comparative Example 4 The difference between this comparative example and Example 3 is that the amount of Nb added was 0.017% (less than 0.02%), and all other points are the same as those of Example 3.
[0088] Comparative Example 5 The difference between this comparative example and Example 4 is only in that the amount of Mn element added was 0.18% (less than 0.2%), and all other aspects are the same as those of Example 4.
[0089] Comparative Example 6 The difference between this comparative example and Example 5 is only in that the amount of added Fe element was 0.19% (less than 0.2%), and all other points are the same as those of Example 5.
[0090] Comparative Example 7 The only difference between this comparative example and Example 6 is that the composition by weight is Ni: 20%, Sn: 4%, Si: 1.3%, Al: 3.2%, Nb: 0.6%, Mn: 2.1%, Fe: 2.2%, and the balance is Cu. All other aspects are the same as Example 6.
[0091] Experimental Example The mechanical properties and wear resistance of the multi-component Cu-Ni-Sn-based alloys for oil and gas extraction of Examples 1 to 6, the conventional Cu-15Ni-8Sn alloy of Comparative Example 1, and the Cu-Ni-Sn-based alloys of Comparative Examples 2 to 7 were tested, respectively.
[0092] The tensile strength was tested by a SHIMADZU AG-I250KN precision universal testing machine at a tensile speed of 1 mm / min to obtain the stress-strain curve and tensile strength value of the alloy.
[0093] The elongation test method was to use a Shimadzu AG-I250KN precision universal testing machine to perform a tensile test at a tensile speed of 1 mm / min to obtain the stress-strain curve of the alloy, and an extensometer was used to measure the change in the alloy scale before and after tension to obtain the elongation value.
[0094] The wear rate test method was to use a pin-disk type friction and wear tester to apply different loads and speeds to the manufactured alloy as a pin sample and to perform a dry friction and wear experiment with a small plate. After the friction and wear experiment was performed for a certain time or distance, the mass damage of the alloy pin sample before and after friction and wear was measured, and the wear rate was calculated.
[0095] The mechanical properties and wear resistance of the multi-component Cu-Ni-Sn-based alloys for oil and gas extraction in Examples 1 to 6, the ordinary Cu-15Ni-8Sn alloy in Comparative Example 1, and the Cu-Ni-Sn-based alloys in Comparative Examples 2 to 7 are compared, and are specifically shown in Table 1 below.
[0096] [Table 1]
[0097] The comparative example 1 and the examples 1 to 6 were combined to produce the multi-element Cu for oil and gas extraction of the present invention. The Ni-Sn based alloy has better tensile strength and significantly reduced wear rate compared to the conventional Cu-15Ni-8Sn, making it suitable for application in key components in oil and gas extraction.
[0098] Combining Comparative Example 2 and Example 1, the content of Si element is too low (less than 0.3%), so the effect of suppressing the formation of reverse segregation during alloy solidification is weakened, and the fineness of crystal grains is not significant, which is unfavorable to improving the hot / cold processing performance of the alloy. At the same time, the formation of the NiSi strengthening phase series with Si and Ni is reduced, which reduces the strength of the alloy.
[0099] Combining Comparative Example 3 and Example 2, the content of Al element is too low (less than 0.2%), so that it is difficult to form a series of NiAl strengthening phase with Al element and Ni element, and the alloy strength is greatly reduced.
[0100] Combining Comparative Example 4 and Example 3, it is found that Nb element promotes the amplitude modulation decomposition process of the alloy, improves the resistance recovery and recrystallization softening ability of the alloy, and forms Nb-rich γ phase in the crystal and crystal boundary, which can significantly inhibit the growth of crystal grains and the formation of discontinuous precipitation during the aging process, and improve the strength and wear resistance of the alloy. However, if the Nb content is too low (less than 0.02%), it will weaken the strength and wear resistance of the alloy.
[0101] Combining Comparative Example 5 and Example 4, it was found that Mn element can refine the as-cast grain structure, increase the peak age-hardening strength of the alloy, and inhibit grain boundary reaction and grain coarsening, thereby significantly improving the strength and wear resistance of the alloy. However, if the Mn content is too low (less than 0.2%), it will cause the grains of the as-cast structure to become coarse, thereby weakening the strength and wear resistance of the alloy.
[0102] Combining Comparative Example 6 and Example 5, the addition of trace amounts of Fe can accelerate the deformation heat treatment process of the alloy, and improve the strengthening effect and wear resistance. If the Fe element content is too low (less than 0.2%), it will affect the heat treatment strengthening effect of the alloy, and the strength and wear resistance of the alloy will be reduced.
[0103] Combining Comparative Example 7 and Example 6, the addition of excessive alloying elements, on the one hand, the excess elements cannot be dissolved in the melt casting process, and form coarse second phases that remain in the as-cast structure, resulting in coarse grain size, which is unfavorable for subsequent plastic deformation, and at the same time, a large amount of intermetallic compounds is formed in the heat treatment process, which increases the brittleness of the alloy and greatly reduces the elongation.
[0104] In summary, according to the tensile strength, elongation and wear rate data analysis of the embodiment and comparative example, the present invention uses multi-element micro-alloying to add a variety of alloying elements such as silicon (Si), aluminum (Al), niobium (Nb), manganese (Mn), iron (Fe) to the Cu-Ni-Sn alloy substrate, and under the cooperative use of a variety of elements, the alloy maintains a relatively good elongation rate (elongation rate is more than 3%) while simultaneously improving the strength and wear resistance of the alloy. The tensile strength is more than 1000MPa, and the wear rate is less than 0.1mg / m, which can meet the requirements of the oil and gas extraction industry for the comprehensive performance of the alloy. At the same time, the addition of the above alloying elements can effectively inhibit the segregation of the solidification structure, refine the as-cast structure grains, and favor the subsequent hot extrusion deformation and heat treatment strengthening effect.
Claims
1. 1. A method for producing a multi-component Cu-Ni-Sn-based alloy for oil and gas production, comprising, by weight, 7-20% Ni, 4-12% Sn, 0.3-1.2% Si, 0.2-3.0% Al, 0.02-0.5% Nb, 0.2-2.0% Mn, and 0.2-2.0% Fe, with the balance being Cu, The multi-component Cu-Ni-Sn-based alloy for oil and gas extraction has a tensile strength of 1000 MPa or more, an elongation rate of 3% or more, and a wear rate of 0.1 mg / m or less; First, electrolytic copper is added to a melting furnace, and after the electrolytic copper is completely melted, a Ni source is added, and then a Nb source, a Mn source, a Fe source, and a Si source are added, and finally an Al source and a Sn source are added, and the copper is melted at 1150 to 1250° C. for 30 to 50 minutes, which is step 1; Step 2 is a pouring step in which the molten metal processed in step 1 is made into a mirror-like shape, then left to stand for 1 to 3 minutes, and after the standing is completed, the molten metal is poured into a metal mold, solidified, and an ingot is obtained; Step 3 includes subjecting the ingot to uniform annealing, hot extrusion deformation, solution heat treatment, cold wire drawing deformation and aging heat treatment; In the step 2, the temperature of the pouring is 1200-1300°C, and after the pouring is completed, a step of applying an electromagnetic field to the outside of the metal mold is also included, and the current application range of the electromagnetic field is 20-100A; The temperature of the uniform annealing is 900 to 950°C, the temperature of the hot extrusion deformation is 850 to 950°C, the temperature of the solution heat treatment is 750 to 900°C, the amount of cold wire drawing deformation is 50% to 90%, and the temperature of the aging heat treatment is 300 to 500°C.
1. A method for producing a multi-component Cu-Ni-Sn based alloy for oil and gas production, comprising:
2. The manufacturing method of the multi-component Cu-Ni-Sn-based alloy for oil and gas extraction according to claim 1, characterized in that the contents of trace elements O, S and P in the multi-component Cu-Ni-Sn-based alloy for oil and gas extraction are as follows: O is 5 ppm or less, S is 3 ppm or less, and P is 3 ppm or less, respectively.
3. 3. The method for producing a multi-component Cu-Ni-Sn-based alloy for oil and gas extraction according to claim 2, characterized in that it contains, in weight percent, Ni: 15%, Sn: 8%, Si: 0.8%, Al: 1.2%, Nb: 0.3%, Mn: 0.5%, Fe: 0.5%, and the balance is Cu.
4. In the step 1, the Cu in the electrolytic copper is 99.95 wt % or more, The Ni source is electrolytic nickel, and the Ni content in the electrolytic nickel is 99.96 wt % or more; the Nb source is a Cu-Nb intermediate alloy; the Mn source is a Cu-Mn intermediate alloy; the Fe source is a Cu—Fe intermediate alloy; The Si source is pure silicon, and Si is 99.99 wt% or more; the Al source is pure aluminum, and Al is 99.7 wt % or more; The Sn source is pure tin, and Sn is 99.99 wt% or more. The method for producing the multi-component Cu-Ni-Sn based alloy for oil and gas extraction according to claim 1.
5. In the step 1, in the melting furnace, the melt surface is completely covered with charcoal and deoxidized using a pure phosphorus deoxidizer; In the pure phosphorus oxygen scavenger, the phosphorus content is 99.85% to 99.95%; The amount of the pure phosphorus deoxidizer used is 0.1% to 0.5% of the total weight of the molten metal, The dissolution process also includes the steps of stirring with a graphite stirring rod and scraping off slag with a slag scraping rod. The method for producing the multi-component Cu-Ni-Sn based alloy for oil and gas extraction according to claim 1.
Citation Information
Patent Citations
Preparation method of high-elasticity corrosion-resistant and wear-resistant Cu-Ni-Sn alloy
CN106834795A
High-strength and high-corrosion resistant cooper alloy and preparation method thereof
CN107779660A
Copper alloy material and preparation method thereof
CN114134364A
Copper alloy
JP2016204708A
Cu-Ni-Sn-BASED COPPER ALLOY FOIL, EXTENDED COPPER ARTICLE, ELECTRONIC DEVICE COMPONENT, AND AUTO FOCUS CAMERA MODULE
JP2019065362A